Dielectric properties and ac conductivity behavior of rGO incorporated PVP-PVA blended polymer nanocomposites films. (2022) - Sadiq, Mohd; Hasan Raza, M.M.; Singh, Anjani Kumar; Chaurasia, Sujeet Kumar; Zulfequar, Mohammad; Arya, Anil; Ali, Javid
Abstract: We have reported dielectric and ac conductivity investigations on reduced grapheme oxide (rGO) incorporated PVP-PVA blend polymer nanocomposite films (BPNC) prepared via standard solution casting technique. The dielectric properties and ac conductivity have been explored using the complex electrochemical impedance technique that has been studied at room temperatures. The frequency-dependent dielectric constant (εʹ) is maximum at low frequencies region which value increases with increasing rGO concentration, while at higher frequency region their value decreases with increasing frequency for all BPNC films. The appearance of the loss tangent ( tan δ ) peaks at specific frequency suggested the existence of recline dipoles which has been found to shift towards high frequency side with increasing weight ratios of rGO in all the BPNC films. The fluctation of a.c conductivity behavior as a function of frequency follow Jonscher Power-law model. The a.c. conductivity shows an increasing trend with an increase in the doping concentration of rGO. The electrical modulus has been examined for supporting the complex permittivity part. The relaxation peaks occur in electric modulus (M") indicates the presence of orientation dipoles in the blend polymer nanocomposites, which support the fast ion conduction.